Mobile sensor networks for optimal leak and backflow detection and localization in municipal water networks. (June 2016) - Gong, Weijiao; Suresh, Mahima Agumbe; Smith, Lidia; Ostfeld, Avi; Stoleru, Radu; Rasekh, Amin; Banks, M. Katherine
Abstract: Leak and backflow detections are essential aspects of Water Distribution Systems (WDSs) monitoring and are commonly fulfilled using approaches that are based on static sensor networks and point measurements. Alternatively, we propose a mobile, wireless sensor network solution composed of mobile sensor nodes that travel freely inside the pipes with the water flow, collect and transmit measurements in near-realtime (called sensors) and static access points (called beacons). This study complements the tremendous progress in mobile sensor technology. We formulate the sensor and beacon optimal placement task as a Mixed Integer Nonlinear Programming (MINLP) problem to maximize localization accuracy with budget constraint. Given the high time complexity of MINLP formulation, we propose a disjoint scheme that follows the strategy of splitting the sensor and beacon placement problems and determining the respective number of sensors and beacons by exhaustive search in linear time. Highlights: We present a mathematical model for the joint optimization of sensor and beacon placement to minimize localization error. We propose a computationally less expensive disjoint formulation for sensor and beacon placement. We demonstrate the advantage of our solution on a sample WDS from EPANET and a virtual model city called Micropolis.